STUDY OF ACUTE KIDNEY INJURY IN PREMATURE NEWBORNS AFFECTED BY PERINATAL HYPOXIA - Саврун, Т.І. (World of Medicine and Biology, 2017)
The article presents research findings on the characteristics of acute kidney injury in premature newborns affected by perinatal hypoxia, depending on the gestational age. Clinical manifestations of hypoxic kidney injury were estimated by the severity of edema syndrome, urinary syndrome and hourly diuresis. The study revealed significantly higher levels of cystatin C in blood serum, as well as lipocalin and interleukin-18 (р